PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS IX SMPN 10 PADANG - Putri, Sarah Deriani; Armiati, Armiati (Jurnal Edukasi dan Penelitian Matematika, 2024)
Gaining proficiency in mathematical concepts is a fundamental goal in learning mathematics. However, students' ability to understand mathematical ideas at SMPN 10 Padang is currently inadequate. Applying the Discovery Learning model is an effort to increase student participation in the learning process. This research used quasi-experimental method, specifically using posttest-only non-equivalent control group design. The t-test data analysis resulted in a P-value of 0.013 which indicates that the Discovery Learning model is superior to the direct learning model in class IX SMPN 10 Padang.Keywords– Discovery Learning, Understanding Mathematical Concepts